2014
DOI: 10.1183/09031936.00182813
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue disease-associated pulmonary arterial hypertension in Chinese patients

Abstract: We sought to investigate the characteristics, survival and risk factors for mortality in Chinese patients with connective tissue disease (CTD)-associated pulmonary arterial hypertension (APAH) in modern therapy era.129 consecutive adult patients who visited one of three referral centres in China with a diagnosis of CTD-APAH confirmed by right heart catheterisation during the previous 5 years were enrolled. The end-point was all-cause death or data censoring.Systemic lupus erythematosus was the most common unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
105
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 43 publications
(58 reference statements)
12
105
0
6
Order By: Relevance
“…In patients with SLE, the prevalence of PH was reported with variety from 0.5% to 14% [30], although PH is not common compared with other manifestations. Although SLE was recently reported the most common underline disease in Chinese patients with CTD associated PH [31], our study showed similar prevalence (9.3%) to western data. PH is known to be rare in patients with RA; however, the mean pulmonary artery pressures measured by echocardiography were reported to be elevated and the prevalence of PH was higher in the patients with RA than in healthy controls (21% vs. 4%, respectively) [32].…”
Section: Discussionsupporting
confidence: 75%
“…In patients with SLE, the prevalence of PH was reported with variety from 0.5% to 14% [30], although PH is not common compared with other manifestations. Although SLE was recently reported the most common underline disease in Chinese patients with CTD associated PH [31], our study showed similar prevalence (9.3%) to western data. PH is known to be rare in patients with RA; however, the mean pulmonary artery pressures measured by echocardiography were reported to be elevated and the prevalence of PH was higher in the patients with RA than in healthy controls (21% vs. 4%, respectively) [32].…”
Section: Discussionsupporting
confidence: 75%
“…PAH associated with CTD is the second most prevalent type of PAH after IPAH in Western countries [10]. SSc, particularly in its limited variant, represents the main CTD associated with PAH in Europe and the USA (systemic lupus erythematosus is more common in Asia) [325,329]. The prevalence of haemodynamically proven pre-capillary PH in large cohorts of SSc patients ranges from 5 to 12% [46,325,330,331].…”
Section: Therapymentioning
confidence: 99%
“…Recommendations for PAH associated with CHD are reported in the Table 25. 7.3 Pulmonary arterial hypertension associated with connective tissue disease PAH is a well-known complication of CTDs such as SSc, systemic lupus erythematosus, mixed CTD and, to a lesser extent, rheumatoid arthritis, dermatomyositis and Sjögren's syndrome [325][326][327][328][329]. PAH associated with CTD is the second most prevalent type of PAH after IPAH in Western countries [10].…”
Section: Therapymentioning
confidence: 99%
“…According to Stadie (25), the coincidence of progressive systemic sclerosis and primary biliary cirrhosis seems to be a favorable association for the progression of primary biliary cirrhosis; in this case, the good prognosis of RS could be affected by a pulmonary complication (26).…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have demonstrated that mortality remains high in SSc patients with PAH; more specifically, the three-year survival rate for SSc patients with PAH has been estimated in 56%, compared with 94% in those without PAH, therefore, constituting itself as a leading cause of morbidity and mortality (1) (26,29,30).…”
Section: Discussionmentioning
confidence: 99%